Green synthesis and in silico characterization of 4-Hydroxy-3- methoxybenzaldehyde Schiff bases for insulysin inhibition – a potential lead for type 2 diabetes mellitus - Sridevi Chigurupati, Vasanth Raj Palanimuthu, Suganya Kanagaraj, Sumathi Sundaravadivelu, Venkata Ramaiah Varadharajula (Journal of Applied Pharmaceutical Science, 2021)
The global prevalence of diabetes is likely to increase sharply from 171 million in 2000 and 366 million in 2030. This clearly depicts the frailty of the existing medication for treating diabetes. Organic compounds, especially Schiff bases, flaunt anti-diabetic effects specifically for type 2 diabetes mellitus (T2DM). The research work demonstrates the synthesis of 4-Hydroxy-3-methoxybenzaldehyde Schiff bases following green chemistry and substantiates its activity against T2DM using in silico methods. All the three Schiff bases provide evidence for insulysin inhibition with Pa values more than 0.6 with strict adherence to Lipinski’s rule. Insulysin or insulin-degrading enzyme is a zinc metalloprotease involved in the degradation of insulin and is signified to be a diabetes susceptibility gene. Molecular docking studies with the synthesized Schiff bases against insulysin (3E4A) reveal that compounds S2 and S3 exhibit better binding and affinity than the natural inhibitor ML345.
Keywords: Insulin degradation, molecular docking, activity prediction, Schiff base, diabetes.